ANALISIS FRAMING PEMBERITAAN CITAYAM FASHION WEEK - Rekayatul Akma; Zamroji, Imam (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2023)
Research Objectives: Revealing the framing carried out by two online media, namely Republika.co.id and Kompas.com in viewing the activities of implementing Citayam fashion Week. Reserch Methodology: Qualitative methods. Research Results: Reporting on Citayam Fashion Week on two online media Republika.co.id and Kompas.com July 2022 edition. In their presentation, the two media have differences in their framing processes, this can be seen based on the results of framing analysis. The method used in analyzing the contents of the media text uses the theory of Robert N. Entman. Entman sees framing in two dimensions: selection of issues and emphasizing or highlighting certain aspects of the issue. These two factors can sharpen news framing through the process of selecting issues that are worthy of being displayed and emphasizing the content of the news. According to Entman, framing can be done in four ways: Problem Identifications, Causal Interpretation, Moral Evaluation, Treatment Recommendation. Based on Entaman’s theory in looking at the framing of the two media, the results of the framing on the two media will be known. Conclusion: Republika.co.id, which is an Indonesian Muslim medium, tends not to support CFW activities. This can be seen from the various news reports published by Republika.co.id which highlight the criticism of the MUI leadership, Muhammadiyah central leadership where they feel that CFW activities have had a negative impact for the younger generation. As for Kompas.com, it displays the news by supporting CFW activities. This can be seen from some reports stating that CFW is the creativity of young people.